Toward truly intelligent information systems-from expert systems to automatic programming - Ohsuga, Setsuo (Knowledge-based systems, 1998)
The objective of this paper is to discuss a way of designing intelligent systems that assure autonomy, generality and practicality in problem solving to the greatest extent and can solve complex problems. There are various types of problem solving, depending on the object, and often more than one subjects concern the same problem with different roles in complex problem solving. In order to achieve our goal in this environment, a new architecture for the system and a new modeling scheme for representing problems including human activity are discussed, as well as a way of generating problem-specific problem solving systems. Several new concepts are included in this paper: a multi-level function structure and its corresponding knowledge structure, multiple meta-level operations, a multi-strata model to represent problems including human activity, etc. It is shown that the system realizes not only the generality but also the practicality of problem solving by enabling automatic programming.